Analysis of miR‐146a and miR‐142‐3p as Potential Markers of Freshly Isolated or In Vitro‐Expanded Human Treg cells. (February 2017) - Holmstrøm, K.; Pedersen, A. E.; Gad, M.
Abstract: Regulatory CD4 + T cells (Tregs) are pivotal for prevention of autoimmunity. The use of Tregs is therefore of increasing interest in in vitro drug screening assays as well as for a cytotherapy per se against autoimmune disorders. For both purposes, in vitro expansion of peripheral blood Tregs is necessary and there is an increasing need to identify novel markers that can discriminate natural thymic‐derived Tregs (tTregs) from other T cell subsets, and ideally, such markers should be stably expressed during in vitro expansion procedures. We screened for novel miRNAs differentially expressed in tTregs and identified miR‐146a and 142‐3p as possible candidates. We analysed freshly isolated naïve and activated tTregs and non‐Treg subsets after or prior to in vitro expansion. We observed a tTreg‐specific profile of these miRNAs together with FOXP3 and Helios in freshly isolated tTregs, but observed a decline in the same markers in activated tTregs as opposed to naïve tTregs. In vitro ‐expanded Tregs could be identified based on FOXP3 expression, but with loss of a discriminate profile for miRNA candidates and a decline in FOXP3 when activated tTregs were expanded. Our data demonstrate miR‐146a and 142‐3p as potential miRNA markers for discrimination between non‐Treg cells and tTregs, but these miRNAs are not stable markers for in vitro ‐expanded Treg cells. In addition, the loss of FOXP3 in expansion of activated tTregs has implication for in vitro use of this cell subset in immunopharmacological assays and cytotherapy as FOXP3 is pivotal for suppressive function.